5‐aminolaevulinic acid/photo‐dynamic therapy and gefitinib in non‐small cell lung cancer cell lines: a potential strategy to improve gefitinib therapeutic efficacy. (21st July 2013) - Postiglione, I.; Chiaviello, A.; Aloj, S. M.; Palumbo, G.
Abstract Objectives Often, non‐small cell lung cancers (NSCLC) respond only poorly to the tyrosine kinase inhibitor (TKI) gefitinib, which targets the epidermal growth factor receptor (EGFR), these poor responders EGFRs lacking activating mutations. In this study, we have attempted to improve TKI response of NSCLC cell lines (A549 and H1299) devoid of EGFR mutations, by combination of gefitinib and 5‐ALA/photodynamic therapy (PDT). Materials and methods Cells of the two lines were incubated with gefitinib (from 0.5 to 50 mm, for 48 h) then irradiated at doses ranging from 4 to 20 J/cm2; 5‐ALA concentration and incubation time were kept constant (1 mm for 3 h). We analysed cell viability, colony‐forming efficiency, cell cycle parameters, proteasome and NF‐κB activity and expression patterns of specific proteins, after individual or combined treatments. Results Effects (antagonistic, additive or synergistic) of combination treatment were evaluated using a predictive model (combination index) for expected interactive effects and results are consistent with mutual potentiation exceeding simple additivity. Investigation of molecular mechanisms underlying cytotoxic effects indicated that combination treatment impaired proteasome function, inhibited NF‐κB transcriptional activity and hampered AKT pro‐survival signalling. Conclusions The results of this study show that poor response of cells devoid of EGFR activating mutations to TKIs, can be overcome by combining gefitinib with 5‐ALA/photodynamic therapy (PDT).